The Parlour and the Suburb: Domestic Identities, Class, Femininity and Modernity - Belisle, Donica (Labour / Le Travail, 2008)
The article reviews the book, "The Parlour & the Suburb: Domestic Identities, Class, Femininity and Modernity," by Judy Giles.
Keywords: BOOKS -- Reviews; GILES, Judy; Nonfiction; PARLOUR & the Suburb: Domestic Identities, Class, Femininity & Modernity, The (Book); WOMEN in development